2018
DOI: 10.1080/20008198.2018.1472988
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular and psychological responses to voluntary recall of trauma in posttraumatic stress disorder

Abstract: Voluntary recall of trauma is a key element in exposure-based psychotherapies and can trigger spontaneous dissociative responses such as flashbacks, depersonalisation, and derealisation. In order to examine the associations between cardiovascular and psychological responses to voluntary recollection of trauma, individuals with PTSD recalled a traumatic memory. Heart rate and heart rate variability were recorded continuously and the episodes when different forms of dissociation were experienced during the recal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 49 publications
2
16
1
Order By: Relevance
“…Thalamic deactivation has been proposed as a mechanism whereby dissociative symptoms can emerge during symptom provocation (Krystal et al, ). Furthermore, individuals eliciting dissociative responses across multiple disorders (i.e., PTSD, borderline personality disorder, depersonalization disorder, dissociative identity disorder) exhibit a lack of autonomic response during states of depersonalization and/or derealization, as measured by reductions in heart rate variability and decreased startle responses (Chou, Marca, Steptoe, & Brewin, , ; Lanius et al, ; Sierra et al, ; for a review, see Owens, Low, Iodice, Mathias, & Critchley, ). Although there is no experimental evidence to state conclusively that motor paralysis occurs during emotional shutdown responses in PTSD, current evidence surrounding dissociation suggests that shutdown responses can be engaged during traumatic episodes and their subsequent recall.…”
Section: Emotional Shutdownmentioning
confidence: 99%
“…Thalamic deactivation has been proposed as a mechanism whereby dissociative symptoms can emerge during symptom provocation (Krystal et al, ). Furthermore, individuals eliciting dissociative responses across multiple disorders (i.e., PTSD, borderline personality disorder, depersonalization disorder, dissociative identity disorder) exhibit a lack of autonomic response during states of depersonalization and/or derealization, as measured by reductions in heart rate variability and decreased startle responses (Chou, Marca, Steptoe, & Brewin, , ; Lanius et al, ; Sierra et al, ; for a review, see Owens, Low, Iodice, Mathias, & Critchley, ). Although there is no experimental evidence to state conclusively that motor paralysis occurs during emotional shutdown responses in PTSD, current evidence surrounding dissociation suggests that shutdown responses can be engaged during traumatic episodes and their subsequent recall.…”
Section: Emotional Shutdownmentioning
confidence: 99%
“…As Janet stated more than a century ago: “mental health is characterized by a high capacity for integration” (Janet, 1889 page 460). The disintegrative processes lead to a wide range of different psychopathological phenomena depending on which mental function they compromise: from alterations of self-consciousness, such as detachment symptoms (derealization/depersonalization), to the fragmentation of self-experiences, such as compartmentalization symptoms (e.g., amnesia, motor control, and multiple personality), and even to a sudden loss of control on emotions and behavior and vegetative arousal dysregulation (Carlson et al., 2009; Farina and Liotti, 2013; Chou et al., 2018).…”
Section: Dissociation and Disintegrative Traumatic Processesmentioning
confidence: 99%
“…Like the real-life situations PTSD patients encounter, the same words and phrases tend to elicit flashbacks repeatedly, but not invariably—flashback elicitation is a probabilistic rather than a wholly predictable process. A recent study of the voluntary recall of trauma memories by a PTSD sample, mimicking what happens in exposure therapy, found that whereas heart rate gradually reduced over time, flashbacks were accompanied by momentary increases in heart rate [ 39 ].…”
Section: Memory Modelsmentioning
confidence: 99%